REPOSITORY PERPUSTAKAAN BERBASIS ANDROID DI UNIVERSITAS MUHAMMADIYAH GORONTALO - Lamusu, Rizal; Lasaruddin, Alter; Ibrahim, Irawan; Lestari, Gita (Universitas Muhammadiyah Gorontalo, 2023)
This research was conducted with the aim of developing the Repository application, initially the system was more directed to journal searches, did not provide reading access rights, no journal download feature and the information was still incomplete so that it would be developed using Android-based technology. Through this research, it is hoped that the journal search process wil be much more this application was developed using the SDLC system development method or Software Development Life Cycle which has several stage, namely Planning, Analysis, Design and Implementation. By using system testing Black-box type Boundry Value Analysis/Limit Testing. The result of this research are in the form of an Android-based library repository application software.